2013
DOI: 10.1371/journal.pone.0075749
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Correlation between Bacterial Cold Water Disease Resistance and Spleen Index in a Domesticated Population of Rainbow Trout: Identification of QTL on Chromosome Omy19

Abstract: Selective breeding of animals for increased disease resistance is an effective strategy to reduce mortality in aquaculture. However, implementation of selective breeding programs is limited by an incomplete understanding of host resistance traits. We previously reported results of a rainbow trout selection program that demonstrated increased survival following challenge with Flavobacterium psychrophilum, the causative agent of bacterial cold water disease (BCWD). Mechanistic study of disease resistance identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 54 publications
(81 reference statements)
6
46
0
Order By: Relevance
“…The splenosomatic values observed in this study were all slightly higher than those reported for rainbow trout in a number of other studies [24 -27], but were very similar to those observed in one other study [28,29], and well within normal values [30]. Thus, the small, but significant difference, in splenosomatic index among the treatments was likely not biologically significant.…”
Section: Discussionsupporting
confidence: 85%
“…The splenosomatic values observed in this study were all slightly higher than those reported for rainbow trout in a number of other studies [24 -27], but were very similar to those observed in one other study [28,29], and well within normal values [30]. Thus, the small, but significant difference, in splenosomatic index among the treatments was likely not biologically significant.…”
Section: Discussionsupporting
confidence: 85%
“…R-line fish have lower pathogen loads after challenge with Fp by intraperitoneal injection (Hadidi et al, 2008) and exhibit higher survival by 5–10 days post-infection (Wiens et al, 2013a) suggesting enhanced capacity for pathogen control relative to the S-line. Resistance to Fp has also been correlated with naive animal spleen size (Hadidi et al, 2008), with Fp-resistant trout having larger spleens (Wiens et al, 2013b)(Wiens et al, 2013c), although its functional significance remains unclear, as splenectomized animals do not show changes in resistance to Fp (Wiens et al, 2015). We have also reported on differences in humoral immunity between the lines, with naïve R-line trout having lower abundance of IgM + and IgM ++ cells (ISCs) compared to S-line fish (Zwollo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor inhibition rate was calculated as follows: Inhibition (%)=(C-T)/C x 100%, where C and T represent the tumor weights (in mg) of control and treated mice, respectively. Based on the correlation between immune activity and the weights of the spleen and thymus, the relative weights of the spleen and thymus (in mg) with regards to the mouse body weight (10 g) were used to obtain the spleen index (SI) and thymus index (TI), as previously described (11,12).…”
Section: Methodsmentioning
confidence: 99%